Shear Stress Analysis and Crack Prevention Measures for a Concrete-Face Rockfill Dam, Advanced Construction of a First-Stage Face Slab, and a First-Stage Face Slab in Advanced Reservoir Water Storage - Kongzhong Hu; Jiankang Chen; Dong Wang (Advances in Civil Engineering)
Due to the demand in flood season for power generation, the first-stage face slab of a high concrete-face rockfill dam often must be constructed ahead of schedule, and advanced water storage is needed for the reservoir. Since the dam-body filling has not yet been completed at this point, the internal stress of the first-stage face slab is more complicated than that of normal construction. Taking Buxi Power Station as an example, the first-stage face slab temporary construction seam showed large areas of shear stress damage during the rise in reservoir water levels during the second segment of the second construction stage. The concrete-face slab showed large-piece brittle bulging, and the steel rebar was exposed and developed contortional deformation. Based on the monitoring data for Buxi Power Station along with the first-stage fracture characteristics of Shuibuya concrete face, this paper applied a numerical analysis to conduct research on the causes of fracture mechanics. The results indicate that the cracks occurred on the face slab during the second segment of second-stage water storage primarily due to the advanced concrete pouring of the first-stage face slab; during the first stage of reservoir water storage, the internal stress of the first-stage face slab was not reduced or eliminated prior to second-stage face slab pouring. Thus, with the rise in the reservoir water level, the shear stress increased continuously, eventually leading to partial large-scale shear stress failure of the first-stage face slab. The research results provide important references for the design and construction of concrete-face rockfill dams.